Penyusunan Standard Operating Procedures (SOP) Pada Dinas Pendidikan Kabupaten Bengkayang Dalam Rangka Peningkatan Mutu Manajemen Organisasi - Herry Sanoto (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2020)
This study aims to prepare SOP for organizational management at Bengkayang Regency Education Office. This research is a qualitative descriptive study with the following steps: (1) preliminary study, (2) planning, and (3) implementation. The subject of this research is Bengkayang Regency Education Office. The data collection techniques used were interviews and observation. The results of interviews and observations were analyzed by reducing data, presenting data, and drawing conclusions. The results of the preliminary study show that the Bengkayang Regency Education Office does not yet have a Standard Operating Procedure (SOP) for organizational management. SOP preparation is carried out by making field notes on mentoring activities and compiling SOP formats. Meanwhile, the implementation of SOP preparation assistance is carried out in six stages, namely the preparation stage, the formation of an implementation team, planning, drafting, testing SOP drafts, and implementing SOP. SOP is needed to regulate quality assurance of organizational management.